Research on the application of on-board energy storage on an electric locomotive for quarry railway transport - Kondratieva, L. Yu.; Overianova, L. V.; Riabov, Ie. S.; Yeritsyan, B. Kh.; Goolak, S. O. (My University, 2023)
Methods of using on-board energy storage system on rolling stock are considered. Their use ensures a reduction in energy consumption and reduces the impact on the environment. Concepts of managing energy flows in the traction system of an electric rolling stock equipped with onboard energy storage systems are considered. It is proposed to apply the concept of control on an electric locomotive for quarry railway transport, which consists in reducing the current consumption from the traction network during the acceleration of the rolling stock and compensating the power during movement with the lowest voltage on the current receiver. For the selected control concept, a simulation of the train movement on the test section was carried out while varying the value of the limit current consumed by the electric locomotive from the traction network. The power of the energy storage device and its working energy capacity is determined. Based on the results of the study, it is justified to limit the current consumed by the electric locomotive of the traction network at the level of 600 A.
Keywords: railway transport; on-board energy storage system; traction electric drive; electric locomotive; accumulators